PREREQUISITES FOR THE DEVELOPMENT OF PUBLIC CATERING ENTERPRISES OF THE LOKAVOR CUISINE ON THE CRIMEAN PENINSULA - M. A. Boyarkina (Современная наука и инновации)
State support for the agro-industrial complex on the Crimean peninsula has led to an increase in the volume of agricultural production. The appearance of a sufficient number of local food products, as well as the desire of the population to eat high-quality products, contribute to the emergence of public catering establishments on the peninsula adhering to the principles of locavoring (regionality, seasonality, preservation of ecology, the use of natural products, support for domestic producers).